Exploring Stó:Lō-Coast Salish Interaction and Identity in Ancient Houses and Settlements in the Fraser Valley, British Columbia. Issue 4 (20th October 2009) - Lepofsky, Dana; Schaepe, David M.; Graesch, Anthony P.; Lenert, Michael; Ormerod, Patricia; Carlson, Keith Thor; Arnold, Jeanne E.; Blake, Michael; Moore, Patrick; Clague, John J.
Abstract : Social scientists recognize a complex and iterative relationship between the built environment and social identities. Here, we explore the extent to which household and settlement remains may be used as archaeological correlates of collective identities among the Stó:lō-Coast Salish peoples of the Fraser River Valley. Using data from six recently tested archaeological sites we begin with the household and explore expressions of identity at various social-spatial scales. The sites span the period from 4200 cal B.C. to the late A.D. 1800s and include settlements with semi-subterranean houses of different forms as well as aboveground plank houses. Across this timeframe we see both change and continuity in settlement location, layout, size, and house form. Our data suggest that although group identities have changed over the millennia, selected social units have persisted through many generations and can be linked to present-day identities of the Stó:lō-Coast Salish.